Implikasi Anak Lahir Di Luar Nikah Terhadap Pemenuhan Hak Pengasuhan Dan Kesejahteraan Psikososial: Studi Di Kabupaten Jepara - Ilham Maulana; Hudi Hudi; Imron Choeri (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Children born out of wedlock raise legal issues regarding the child's rights to care and psychosocial welfare to ensure the child's best interests. This research employs a qualitative approach using library research, complemented by in-depth interviews with family law experts, civil registration officials, and child protection policymakers. The findings indicate obstacles in fulfilling legal identity, a predominance of single-parent caregiving by mothers, and inconsistencies in the implementation of parental responsibilities, which affect children’s psychosocial well-being. The analysis highlights the need for a more substantive and integrated child protection approach. This study concludes that child protection must be oriented toward the best interests of the child and recommends strengthening inclusive and responsive legal and caregiving policies.